Dynamic Programming Optimization of Multi-rate Multicast Video-Streaming Services - Tiglao, Nestor Michael Caños; Monteiro, Janio Miguel E.F.; Grilo, Antonio Manuel R. C.; Nunes, Mario Serafim S.; Xavier, Joao Manuel F. (Science Diliman: A Journal of Pure and Applied Sciences; Vol 22 No 1 (2010), 2011)
Normal 0 21 false false false PT X-NONE X-NONE I n large scale IP Television (IPTV) and Mobile TV distributions, the video signal is typically encoded and transmitted using several quality streams, over IP Multicast channels, to several groups of receivers, which are classified in terms of their reception rate. As the number of video streams is usually constrained by both the number of TV channels and the maximum capacity of the content distribution network, it is necessary to find the selection of video stream transmission rates that maximizes the overall user satisfaction. In order to efficiently solve this problem, this paper proposes the Dynamic Programming Multi-rate Optimization (DPMO) algorithm. The latter was comparatively evaluated considering several user distributions, featuring different access rate patterns. The experimental results reveal that DPMO is significantly more efficient than exhaustive search, while presenting slightly higher execution times than the non-optimal Multi-rate Step Search (MSS) algorithm.
Keywords: Quality of Experience (QoE), Dynamic Programming , Quality of Service (QoS), Internet Protocol Television (IPTV), Multi-Rate